Repurposing radiosensitising medicines for radiotherapy: an overview - Geoff S Higgins; Jie Man Low; Gonzalo Rodriguez-Berriguete (BMJ Oncology)
Repurposing established non-cancer drugs for the treatment of cancer offers potential benefits such as speed of clinical translation and financial efficiencies. In this study, we assess the landscape of repurposing drugs for combined use with radiotherapy (RT) based on their capacity to increase tumour radiosensitivity. Using a literature-based approach, we identified 42 radiosensitising drugs with varied non-cancer indications and mechanisms of action, that have entered or completed clinical trials in combination with RT or with chemoradiotherapy. Two compounds, nicotinamide and nimorazole, have entered routine but limited clinical use in combination with radiotherapy. We provide an overview on these successfully repurposed drugs, and highlight some examples of unsuccessful repurposing efforts and drug candidates with an uncertain prospect of success. Upon reviewing the trials, we identified some common themes behind the unsuccessful efforts, including poor trial reporting, absence of biomarkers and patient selection, sub-optimal pharmacological properties, inappropriate trial design, lack or inadequate consideration of pre-clinical and clinical data, and limited funding support. We point out future directions to mitigate these issues and increase the likelihood of success in repurposing drug treatments for radiotherapy.